Relationship Between Smoking Status and Anger the University of Students - Birsen Durmus, A.; Pirincci, Edibe (Annals of Medical Research, 2021)
Aim: It is a descriptive, cross-sectional research carried out in order to examine the relationship between and smoking status and anger of the students in Firat University, in the college of Health Services.
Keywords: s: University students, Smoking, Trait anger